2014
DOI: 10.7557/3.2608
|View full text |Cite
|
Sign up to set email alerts
|

Use of Multiple Methods to Estimate Walrus (<i>Odobenus rosmarus rosmarus</i>) Abundance in the Penny Strait-Lancaster Sound and West Jones Sound Stocks, Canada

Abstract: Atlantic walrus (Odobenus rosmarus rosmarus) occur in Canada in a number of largely discrete stocks (Born et al. 1995, DFO 2002, COSEWIC 2006, Stewart 2008. In the Canadian Arctic Archipelago there are three recognized stocks (NAMMCO 2006, 2011, Stewart 2008: the Baffin Bay stock, the West Jones Sound stock and the Penny Strait-Lancaster Sound stock. Within the range of each stock, walrus are widely distributed in the open-water season when they are found at sea and on ice or land in numbers from 1 to over 1,0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Therefore, they may be harder to count during real-time observation. Imprecise group size estimates are not uncommon in the presence of numerous simultaneous sightings, and observers tend to underestimate the size of large groups (Norton-Griffiths 1974, Scott et al 1985, Mathews 1995, Lowry 1999, Stewart et al 2013. The tendency to underestimate group size has been observed to increase with group size (Gerrodette et al 2018), although this effect was observed in group sizes (>25 individuals/group) exceeding the ones observed during this survey.…”
Section: Comparison Of Image and Observer Sightingsmentioning
confidence: 62%
See 1 more Smart Citation
“…Therefore, they may be harder to count during real-time observation. Imprecise group size estimates are not uncommon in the presence of numerous simultaneous sightings, and observers tend to underestimate the size of large groups (Norton-Griffiths 1974, Scott et al 1985, Mathews 1995, Lowry 1999, Stewart et al 2013. The tendency to underestimate group size has been observed to increase with group size (Gerrodette et al 2018), although this effect was observed in group sizes (>25 individuals/group) exceeding the ones observed during this survey.…”
Section: Comparison Of Image and Observer Sightingsmentioning
confidence: 62%
“…, Mathews , Lowry , Stewart et al . ). The tendency to underestimate group size has been observed to increase with group size (Gerrodette et al .…”
Section: Discussionmentioning
confidence: 97%
“…Total counts from 20 August (hauled out and at sea) allowed a Minimum Counted Population (MCP, for a definition and description see Stewart et al 2014a). Based on information from the three tagged animals we established adjustment factors to account for the proportion of animals that were not hauled out.…”
Section: Estimating the Number Of Walruses Not Available For Detectionmentioning
confidence: 99%
“…Regression analysis (SigmaStat® v 3.11) was used to assess between-observer counts of photos taken from aircrafts and boats in the Canadian High Arctic during 1998-2008 and along Baffin Island during 2007-2008. These analyses indicated there was little inter-observer variation (Stewart et al 2014a) thus numbers of walruses in photographs from the survey in eastern Ellesmere Island in 2009 were counted by one observer (REAS). When there were data of more than one type available for a site, aerial photo-count was preferred over a visual estimate.…”
Section: Counting Walrusesmentioning
confidence: 99%
See 1 more Smart Citation